2020
DOI: 10.1097/sla.0000000000004216
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Broad-spectrum Antibiotics are Associated With Decreased Surgical Site Infections Compared to 1st–3rd Generation Cephalosporins After Open Pancreaticoduodenectomy in Patients With Jaundice or a Biliary Stent

Abstract: Objective: Compare the effectiveness of 1st-3rd generation cephalosporins (1st-3rdCE) to broad-spectrum antibiotics in decreasing surgical site infections (SSI) after pancreatectomy. Summary of Background Data: SSI is one of the most common complications after pancreatic surgery. Various antibiotic regimens are utilized nationwide with no clear guidelines for pancreatectomy. As we await results of a recently initiated prospective trial, this study retrospectively evaluates over 15,000 patients using the same a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…48 Among those who underwent biliary instrumentation or had preoperative jaundice, broad-spectrum antibiotics was associated with a decrease on overall rates of SSIs (24% vs 19%, P ¼ 0.001). 48 Together, these studies suggest that targeted broadspectrum antibiotics may be particularly important in those undergoing PBD.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…48 Among those who underwent biliary instrumentation or had preoperative jaundice, broad-spectrum antibiotics was associated with a decrease on overall rates of SSIs (24% vs 19%, P ¼ 0.001). 48 Together, these studies suggest that targeted broadspectrum antibiotics may be particularly important in those undergoing PBD.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, Okamura and colleagues 28 demonstrated a reduction in postoperative SSIs in those receiving targeted antibiotics ( P = 0.012) despite this group having more patients with preoperative cholangitis. In addition, a recent retrospective study comparing the use of cephalosporins versus other broad-spectrum antibiotics found that patients without biliary drainage have similar rates of SSIs regardless of antibiotic choice 48 . Among those who underwent biliary instrumentation or had preoperative jaundice, broad-spectrum antibiotics was associated with a decrease on overall rates of SSIs (24% vs 19%, P = 0.001) 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krüger et al found that the prevalence of resistance in bacteriobilia was 50% for cefotaxime vs 26% for piperacillin‐tazobactam 34 . A study from the American College of Surgeons National Surgical Quality Improvement Program database analyzing 15 182 pancreatic surgeries found that patients with biliary endoprosthesis who received perioperative prophylaxis with broad‐spectrum antibiotics had a decreased risk of postoperative complications than patients who received 1st‐ to 3rd‐generation cephalosporins 35 . A randomized controlled trial comparing cefoxitin and piperacillin‐tazobactam as antibiotic prophylaxis in all patients undergoing pancreaticoduodenectomy is ongoing (NCT03269994).…”
Section: Discussionmentioning
confidence: 99%
“…34 A study from the American College of Surgeons National Surgical Quality Improvement Program database analyzing 15 182 pancreatic surgeries found that patients with biliary endoprosthesis who received perioperative prophylaxis with broad-antibiotics had a risk of postoperative complications than patients who received 1st-to 3rd-generation cephalosporins. 35 A randomized controlled trial comparing cefoxitin and piperacillintazobactam as antibiotic prophylaxis in all patients undergoing pancreaticoduodenectomy is ongoing (NCT03269994). The composition of gut microbiome may be associated with increased risk of surgical complications, including anastomotic fistula or adhesions.…”
Section: Risk Factors For Deep Infectious Complications In Patients W...mentioning
confidence: 99%